Introduction to the novel techniques in microscopy feature issue - Potma, Eric O. (Biomed Opt Express, 2015)
The editors introduce the feature issue on “Novel Techniques in Microscopy,” which was the topic of a symposium held on April 12–15, 2015, in Vancouver, BC. This symposium was part of the Optics in the Life Sciences Congress.